Comment on the paper "Application of homotopy analysis method to solve MHD Jeffery–Hamel flows in non-parallel walls, S.M. Moghimi, G. Domairry, Soheil Soleimani, E. Ghasemi, H. Bararnia, Advances in Engineering Software 42 (2011) 108–113". (April 2017) - Pantokratoras, Asterios
Highlights: The problem concerns Jeffery–Hamel flow in non-parallel walls. The momentum equation is wrong. The Hartmann number is wrong. Abstract: The present comment concerns some doubtful results included in the above paper.